RESEARCH OF PHYSICAL AND MECHANICAL PROPERTIES OF BASALT FIBER CONCRETE - M. Ashurov; Rakhimov Rasuljon Ravshanbek o‘g‘li (Journal Park Publishing, 2023)
This article describes the analysis of the results of research on the composition and properties of concrete with basalt fibers and the mixture without basalt fibers. The article provides information on the optimal composition of basalt fiber for concrete.
Keywords: Basalt, fiber, fiber concrete, fiber, construction.